1989
DOI: 10.1210/endo-124-5-2449
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Hippocampus in Central Nervous System-Mediated Glucoregulation in Rats

Abstract: To find out whether the hippocampus is involved in central nervous system-mediated glucoregulation, we injected saline, neostigmine, dopamine, norepinephrine, bombesin, beta-endorphin, somatostatin, and prostaglandin F2 alpha into the dorsal hippocampus in anesthetized fed rats. After injection of dopamine, norepinephrine, bombesin, beta-endorphin, somatostatin, or prostaglandin F2 alpha, the level of hepatic venous plasma glucose did not differ from that in saline-treated control rats. However, neostigmine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…We have previously reported that the hippocampus was involved in CNS-mediated glucoregulation through cholinergic muscarinic activation [1], based on the fact that microinjection of neostigmine into the dorsal hippo campus leads to hepatic venous hyperglycemia associated with increased levels of glucagon, epinephrine, and nor-47 Table 3. Hepatic venous plasma epinephrine (pg/ml) and norepinephrine (pg/ml) concentrations following microinjection of saline alone 0.2 pi or saline with 5 x 10~8 mol neostigmine into the hippocampus…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously reported that the hippocampus was involved in CNS-mediated glucoregulation through cholinergic muscarinic activation [1], based on the fact that microinjection of neostigmine into the dorsal hippo campus leads to hepatic venous hyperglycemia associated with increased levels of glucagon, epinephrine, and nor-47 Table 3. Hepatic venous plasma epinephrine (pg/ml) and norepinephrine (pg/ml) concentrations following microinjection of saline alone 0.2 pi or saline with 5 x 10~8 mol neostigmine into the hippocampus…”
Section: Discussionmentioning
confidence: 99%
“…Forty-five minutes later, rats were placed on a stereotaxic appa ratus, and 0.2 pi of saline with or without neostigmine (5 x I O'8 mol, Sigma Chemical Co., St. Louis, Mo.) was injected unilaterally into the dorsal hippocampus, as previously described [1],…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations